Playing online videogames—more than just entertainment? A qualitative study of virtual social participation in persons with spinal cord injury - Nilsen, R.; Johansen, T.; Løvstad, M.; Linnestad, A. M. (Frontiers in Rehabilitation Sciences, 2024)
Introduction Spinal cord injury (SCI) affects many aspects of life, physically, emotionally and socially. Engaging in online videogames holds the potential to facilitate increased social interactions for individuals with SCI. The aim of this study is to increase our understanding of the experiences people with SCI have with using online videogames as an arena for social participation. Methods A focus group interview was conducted with seven participants with SCI, aged 15–35, all experienced in using online videogames as a method of socializing. The data was analyzed using thematic analysis. Results The participants highlighted that playing online videogames way of maintaining social connections and expanding their social network. However, they faced challenges due to limited knowledge and negative attitudes from others regarding use of videogames as a social arena. Three main themes were developed from the findings: “Disabling social barriers”, “Attitudes towards gaming” and “Gaming—connecting people”. Conclusion Healthcare professionals should consider videogames as a leisure activity and facilitate their use, recognizing their potential for social interaction and well-being. Prioritizing activities that promote social interaction is crucial for good health.